Early success is key to winning an IRB Sevens World Series - van Rooyen, M.; Gerrard, B.; Keogh, J. (International Journal of Sports Science and Coaching, 2015)
The Rugby Sevens World Series concludes with the team who accumulated the most points in the season being crowned champions. The objective of every team is to win their matches, but it is questionable whether winning every tournament is essential to winning a Series. The purpose of this study was: i) to determine the number points that must be accumulated in order to win the Series and if the sequence of point accumulation was important; and ii) to determine the performance of the 5 most successful nations between 1999/2000 and 2011/2012. Data collected from the IRB Sevens website included the Series points scored after each tournament and at the end of the season and the tier (Cup, Plate, Bowl or Shield) of the last match played for the Series winner, 2nd and 3rd placed teams and New Zealand, Fiji, South Africa, Samoa and England. Winners accumulated 83.5% (± 5.5) of the points available per season, 2nd and 3rd teams had 69.9% ± 8.1 and 61.2% ± 4.6 points respectively. New Zealand averaged 76.9% ± 13.8, Fiji 65.5% ± 12.3, South Africa 55.8% ± 12.1, England 50.8% ± 21.5, and Samoa 49.3% ± 17.5. Winning teams (and New Zealand and Fiji) accrued points faster than other teams with over 50% of points won at halfway point in the season. New Zealand had the greatest probability of winning cup quarter or final matches; Fiji was more likely to win semi-finals. No team has won every tournament during a season but a successful start is vital for a Series winner.